PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA PLATINUM RESTORAN PLAZA FESTIVAL - Dewi Apriyanty; Salman Paludi (Eduturisma, 2023)
This study ainsto analyze the effect of service quality, product quality, and location on purchasing decisions at Platinum Restaurant Plaza Festival. This research was conducted on consumers of Platinum Restaurant Plaza Festival during March - April 2023. This research used a quantitative method, primary data obtained from questionnaires using the accidental sampling method of 100 respondents consisting of consumers who had visited. The data is then measured through validity and reliability tests. Meanwhile, for the method of data analysis using multiple linear analysis using IBM SPSS 24, followed by an analysis of the correlation coefficient and determination. From this study, the results show that service quality, product quality, and location have a significant effect on purchasing decisions.